2019
DOI: 10.1088/1742-6596/1378/2/022062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Manual Strapping Method (MSM) and Electro-Optical Distance Ranging (EODR) Method of Tank Calibration

Abstract: Oil storage tanks are mandated for calibration before putting to use and to be recalibrated as a statutory requirement at every five year interval. Oil tanks could be calibrated by geometrical methods such as Manual Strapping Method (MSM) and Electro-Optical Distance Ranging (EODR) method. This study compares both MSM and EODR in terms of cost incurred, duration of calibration and efficiency. Both methods were found to be efficient as they satisfied 95% minimum efficiency as stated by API MPMS 2.2 standard whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The strapping method uses steel meter standards [4][5][6] and optical methods that use theodolite or total station standards [7][8][9][10] that are located in outside of the tank. For the inside of the tank, a comparison of the two methods above has been produced, but it is not stated which method is better [11]. Strapping method testing requires more time and more personnel compared to the optical method.…”
Section: Introductionmentioning
confidence: 99%
“…The strapping method uses steel meter standards [4][5][6] and optical methods that use theodolite or total station standards [7][8][9][10] that are located in outside of the tank. For the inside of the tank, a comparison of the two methods above has been produced, but it is not stated which method is better [11]. Strapping method testing requires more time and more personnel compared to the optical method.…”
Section: Introductionmentioning
confidence: 99%
“…Any inaccuracy can cause problems in the supply chain. The use of known methods [18,19] and controlled measuring instrument characteristics allows for a valid fuel quantity assessment process [20]. Different parties in the performed commercial transactions agree on the different measuring instruments and methods used in the workflow and the interpretation of possible measurement errors [15].…”
Section: Introductionmentioning
confidence: 99%
“…These calibration results are usually displayed in the form of table volume per height. Previous studies showed that the vertical cylinder tank was calibrated by two methods namely the Manual Strapping Method (MSM) [3] and Electro-optical distance ranging (EODR) [4]. Higher cost of EODR calibration than MSM [3].…”
Section: Introductionmentioning
confidence: 99%
“…Higher cost of EODR calibration than MSM [3]. However, EODR takes a much shorter time [4]. Considering this measuring time, another study showed that 3D laser scan technology provided a much shorter time than EODR [5].…”
Section: Introductionmentioning
confidence: 99%